Analysis of the state of dendroflora of park zones in Poltava concerning its its lesion by mistletoe (Viscum album L.) - Pysarenko, V.; Pishchalenko, M.; Barabolia, O.; Krasota, O.; Muler, M. (Scientific Progress & Innovations, 2023)
Mistletoe (Viscum album L.) white is the only plant on the Earth that has a unique substance that paralyses cancer cells and simultaneously stimulates human immunity. However, despite its curative properties, mistletoe white has so far caused considerable damage to tree plantations in human settlements, acting not only as a parasitic plant, but also as a spreader of various diseases of woody plants. Mistletoe, being an inseparable component of tree plantations, both natural and urbanized ecosystems, settling on trees. Then it begins to destroy them intensively. This is why the question of protection of trees from mistletoe white is relevant at present. The purpose of the article is research the state of tree species in park zones of Poltava concerning their damage by white mistletoe (Viscum album L.). The article presents the results of the analysis of the state of the main tree species of the park zones of Poltava city of concerning their lesion by white mistletoe during 2017‒2022. According to the results of the study identified tree species, which due to their species biologo-physiological features are affected more and vice versa show greater resistance to damage by mistletoe white (Viscum album L.). Recommendations for improving the species composi-tion of tree species in park areas of Poltava, taking into account their resistance to mistletoe white damage, have been formulated. For the first time, we studied the degree of damage to deciduous trees in the park areas of Poltava, and set the degree of damage to trees affected by white mistletoe depending on their species biology and physiology, particularly, the structure and thickness of the bark. The influence of species-specific biologic and physiological features of tree species in the park areas of Poltava on the degree of their lesion by mistletoe white has been estab-lished. The most resistant woods have been determined, which can be recommended for renewal of the species composition of the dendroflora of the park zones of the urban ecosystem.